Pandemi ile Evde Yaşam: Covid-19 Süreci ve Sonrası İçin Konut Tasarım Stratejileri - ÖZBEK, DERYA ADIGÜZEL; Eke, Armağan Seçil Melikoğlu (Yildiz Technical Univ., 2022)
Makalenin temel amacı, koronavirüs hastalığı-19 (COVID-19) pandemi sürecinde evlerde yaşanan değişim ve dönüşümlerin sorgulandığı araştırma süreci sonunda, mevcut konut stokunun kullanım olanakları ve yeni yapılacak konutlar için ortaya konulan tasarım stratejilerini tartışmaya açmaktır. Bu doğrultuda, COVID-19 sürecinin evlerde neden olduğu değişimler, talepler ve beklentiler nitel ve nicel araştırma tekniklerinin bir arada diyalektik bir yapı içinde kullanıldığı araştırma tasarımı ile sorgulanmıştır. Araştırmadan elde edilen sonuçlar bütüncül olarak analiz edilerek, mevcut konut stokunun kullanım olanakları ve yeni yapılacak konutlar için tasarım stratejileri geliştirilmiştir. Tasarım stratejileri farklı olasılıkları ve olanakları tartışmaya imkân vermesi için kurgulanan üç adet Ev + [COVID] çalıştayı kapsamında geliştirilmiştir. Bu çalıştaylarda öğrenciler tarafından, mekâna müdahale biçimleri, çoklu kullanım senaryoları, hijyen sistemleri ve iç-dış ilişki çözümleri olmak üzere dört tasarım stratejisi, tasarım önerilerine dönüştürülmüştür. Tasarım stratejilerinin odağına baktığımızda pandemi öncesi konutta mobilya ve dekorasyon düzeyinde kalan kullanıcı müdahalelerinin kapsamının genişletilmesine ihtiyaç duyulduğu anlaşılmaktadır. Kullanıcının ihtiyaç duyduğu değişikliği yapmasını olanaklı kılacak düzeyde dönüştürülebilir ve değiştirilebilir sistemsel çözümlere gereksinim vardır. Araştırmadan tasarım stratejisine uzanan bu çalışma ile araştırma sonuçları konut tasarım ve üretim alanı için uygulanabilir tasarım stratejilerine dönüştürülmüştür. Çalışma ile konut tasarımına odaklanan profesyonel uygulayıcılar için bu kapsamda ortaya konulan bilgiler bir rehber niteliği taşımakta, tasarım stratejileri konut tasarım ve uygulamasına yön verme potansiyeli taşımaktadır.

People's lives are changing rapidly with the Covid-19 outbreak, which was declared as a "pandemic" by the World Health Organization (WHO). Although almost two years have passed since the beginning of the pandemic, the process affects the economy, social relationships, education, spaces, working conditions; in short, the whole life, especially public health, and makes people question what is known as the truth in all disciplines. While lives fit into the home, houses are undergoing a multi-component change in parallel. It is foreseen that after the epidemic, different spatial realities and meanings imposed on houses will be demanded to meet different spatial needs, as well as to create a new atmosphere in the houses. The main purpose of the article is to discuss the possibilities of usage of the existing housing stock and the design strategies for new houses to be built at the end of the research process in which the changes and transformations in houses during the COVID-19 pandemic process are questioned. In this direction, the changes, demands, and expectations caused by the COVID-19 process in homes have been questioned with the research design in which qualitative and quantitative research techniques are used together in a dialectical structure. In the first step of the research design, the survey technique, which is a quantitative research method, was applied in line with the conceptual framework of the study, and then the data obtained in the first step were deepened with semi-structured interviews, which is a qualitative research technique. The results obtained from the research were analysed holistically, and the possibilities of using the existing housing stock and the design strategies for the new houses to be built were developed. The design strategies were developed within the scope of the Home + [COVID] workshops, which were organised at three different levels to allow discussion of different probabilities and possibilities. The workshops were held with the contribution of lecturers and professional partners, with the participation of architecture and interior architecture students in undergraduate and graduate courses on housing and space for different purposes. An informal dimension was brought into a course in formal education by integrating the workshop setup into it, while the theoretical knowledge obtained through research was transformed into design practice. Thus, a multi-layered process model from research to design has been developed. The research findings showed the changes in the houses during the COVID-19 process, the psycho-social and physical condition of the house, the hygiene measures added to the house during this process, the social life needs, remote working and distance education situations and their reflections on the space. The research showed that although the participants stated that they did not need the spatial arrangements they made due to the uncertainty of the pandemic's processes, they felt the desire to continue and the need to act for the future in order to adapt to the situations that emerged due to the pandemic. In addition, the changing expectations of the participants on housing were achieved through the experience gained in this process. These findings were transformed into design proposals under four design strategies as, Space Intervention Styles, Multiple use scenarios, Hygiene systems and Internal-external Relationship Solutions, in three workshops organised at different levels. When we look at the focus of design strategies, it is understood that there is a need to expand the scope of user interventions at the level of furniture and decoration in the pre-pandemic housing. Users feel the need to intervene and control their houses systematically as a result of the radical transformations experienced in homes with COVID-19, increasing functions and usage patterns. There is a need for transformable and changeable systemic solutions that will enable the user to make the changes they need. In this context, design strategies have been developed to expand the scope of user interventions in residential spaces and furniture. With this study, which extends from research to design strategy, the research results are transformed into applicable design strategies for residential design and production. For professional practitioners focusing on housing design, the information revealed within the scope of the study is a guide. On the other hand, the effects of the COVID-19 virus continue, and the time cycle and its reflection on the home space are changing with different quarantine measures. In these ongoing processes, the need and importance of the design strategies developed within the scope of the study increases.
Life at Home With the Pandemic Design Strategies of Housing, for During and After the Covid-19
Keywords: Covid-19; Ev; Konut; Tasarım Araştırması; Tasarım Stratejisi